2015
DOI: 10.1002/cam4.569
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year analysis from phase 2 trial of “sandwich” chemoradiotherapy in newly diagnosed, stage IE to IIE, nasal type, extranodal natural killer/T‐cell lymphoma

Abstract: The “sandwich” protocol, was first proposed by us and comprised of l‐asparaginase, vincristine, and prednisone chemotherapy with radiotherapy, results in 2‐year overall survival and progression‐free survival rates that surpass traditional therapies for patients with newly diagnosed, stage IE‐IIE, nasal type, extranodal natural killer/T‐cell lymphoma. The results had been published by cancer. These patients were followed up over a median period of 67 months, for which updates and the results of prognostic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 24 publications
2
39
0
1
Order By: Relevance
“…Asparaginase‐based or pegaspargase‐based regimens provided favorable outcomes in newly diagnosed and relapse/refractory ENKL, nasal type . Several phase II studies with asparaginase‐based or pegaspargase‐based regimens combined with early RT has been shown to be effective for the treatment of newly diagnosed stage I/II ENKL . However, the toxicity profiles of above regimen limited its wide range of clinical application, especially for early‐stage ENKL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asparaginase‐based or pegaspargase‐based regimens provided favorable outcomes in newly diagnosed and relapse/refractory ENKL, nasal type . Several phase II studies with asparaginase‐based or pegaspargase‐based regimens combined with early RT has been shown to be effective for the treatment of newly diagnosed stage I/II ENKL . However, the toxicity profiles of above regimen limited its wide range of clinical application, especially for early‐stage ENKL.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the gemcitabine alone and/or containing regimen had high clinical activity and low toxicity both in the treatment of T‐cell unspecified lymphoma and in refractory or relapsed NK/T‐cell lymphoma . Meanwhile, the sandwich combined modality therapy has achieved an excellent outcome for localized ENKL with acceptable toxicity . Here, we reported a retrospective study evaluating the efficacy and safety profiles of the sandwich protocol in 72 patients with newly diagnosed stage IE/IIE ENKL, nasal type: an initial 2 cycles of gemcitabine, dexamethasone, and cisplatin (GDP), followed by earlier involved‐field radiation therapy (IFRT), and further 2 to 4 cycles consolidation CT.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year OS and PFS were both 64%. 57 The high systemic failure rate implied that this regimen was not intensive enough to deal with occult dissemination.…”
Section: Sequential Chemotherapy and Radiotherapymentioning
confidence: 99%
“…13 Sandwich chemoradiation (2 cycles of chemotherapy followed by involved-field RT [56 Gy] followed by 2-4 cycles of chemotherapy within 7 days of completion of involved-field RT) with asparaginase-or pegaspargase-based chemotherapy has been shown to be effective for the treatment of patients with newly diagnosed stage I-II ENKL-NT. [38][39][40] In a phase II study of 27 patients, sandwich chemoradiation with GELOX (L-asparaginase/gemcitabine/oxaliplatin) resulted in an ORR of 96% (CR, 74%). After a median follow-up of 63 months, 5-year OS and PFS rates were 85% and 74%, respectively.…”
Section: Nktl-b 2 Of 2 Nccn Guidelines Version 22018mentioning
confidence: 99%